Strategy For Implementing PAMSIMAS Policy Using Jan MerseModel to Elevate Public Health Service Quality (A Case Study in Gorontalo District) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research affords an analysis of a strategy for implementing the Jan Merse public policy model in thePAMSIMAS program and building an ideal model as an alternative strategy for implementing a policy to improve publichealth service quality in Gorontalo District. It is carried out using a descriptive qualitative approach, which requires theresearcher to be the key instrument. Data are collected through observation, structured interviews, documentation studies, andfocus group discussions. Results demonstrate that successful policy implementation, according to Jan Merse’s approach, isaffected by the aspects of information, policy content, organizational supports, community supports, and potency division, aswell as skills, loyalty, and education. Based on the ground condition, it is recommended to use a TARO model approach as analternative strategy for implementing the PAMSIMAS program policy. This model combines the government roles from theaspects of transparency, accuracy, and responsibility with the community roles from the aspect of common ownership.Accordingly, this model is expected to eliminate potential inhibitors of the program. Additionally, this model can assist themaking of the roadmap of village development using the PAMSIMAS program. Eventually, the PAMSIMAS service can bedelivered in a synergetic and integrated avenue and in conforming with the target to cater to the needs of people withdisabilities and decrease local stunting levels.